Analysis of outcomes in ischemic vs nonischemic cardiomyopathy in patients with atrial fibrillation: a report from the GARFIELD-AF registry - Corbalan, Ramon; Hacke, Werner (JAMA cardiology, 2019)
Importance: Congestive heart failure (CHF) is commonly associated with nonvalvular atrial fibrillation (AF), and their combination may affect treatment strategies and outcomes. - Objective: To assess the treatment strategies and 1-year clinical outcomes of antithrombotic and CHF therapies for patients with newly diagnosed AF with concomitant CHF stratified by etiology (ischemic cardiomyopathy [ICM] vs nonischemic cardiomyopathy [NICM]). - Design, Setting, and Participants: The GARFIELD-AF registry is a prospective, noninterventional registry. A total of 52014 patients with AF were enrolled between March 2010 and August 2016. A total of 11738 patients 18 years and older with newly diagnosed AF (≤6 weeks' duration) and at least 1 investigator-determined stroke risk factor were included. Data were analyzed from December 2017 to September 2018. - Exposures: One-year follow-up rates of death, stroke/systemic embolism, and major bleeding were assessed. - Main Outcomes and Measures: Event rates per 100 person-years were estimated from the Poisson model and Cox hazard ratios (HRs) and 95% confidence intervals. - Results: The median age of the population was 71.0 years, 22987 of 52013 were women (44.2%) and 31958 of 52014 were white (61.4%). Of 11738 patients with CHF, 4717 (40.2%) had ICM and 7021 (59.8%) had NICM. Prescription of oral anticoagulant and antiplatelet drugs was not balanced between groups. Oral anticoagulants with or without antiplatelet drugs were used in 2753 patients with ICM (60.1%) and 5082 patients with NICM (73.7%). Antiplatelets were prescribed alone in 1576 patients with ICM (34.4%) and 1071 patients with NICM (15.5%). Compared with patients with NICM, use of angiotensin-converting enzyme inhibitors/angiotensin receptor blockers (72.6% [3439] vs 60.3% [4236]) and of β blockers (63.3% [2988] vs 53.2% [3737]) was higher in patients with ICM. Rates of all-cause and cardiovascular death per 100 patient-years were significantly higher in the ICM group (all-cause death: ICM, 10.2; 95% CI, 9.2-11.1; NICM, 7.0; 95% CI, 6.4-7.6; cardiovascular death: ICM, 5.1; 95% CI, 4.5-5.9; NICM, 2.9; 95% CI, 2.5-3.4). Stroke/systemic embolism rates tended to be higher in ICM groups compared with NICM groups (ICM, 2.0; 95% CI, 1.6-2.5; NICM, 1.5; 95% CI, 1.3-1.9). Major bleeding rates were significantly higher in the ICM group (1.1; 95% CI, 0.8-1.4) compared with the NICM group (0.7; 95% CI, 0.5-0.9). - Conclusions and Relevance: Patients with ICM received oral anticoagulants with or without antiplatelet drugs less frequently and antiplatelets alone more frequently than patients with NICM, but they received angiotensin-converting enzyme inhibitors/angiotensin receptor blockers more often than patients with NICM. All-cause and cardiovascular death rates were higher in patients with ICM than patients with NICM. - Trial Registration: ClinicalTrials.gov Identifier: NCT01090362.
GARFIELD-AF Investigators: Ramon Corbalan, Werner Hacke [und 2110 weitere]
Gesehen am 16.08.2019